4CPS-103 Is there a role for the pharmacist in screening for metabolic syndrome?. (24th March 2020) - Aladawi, R; Prabhu, K; Stewart, D; Ryan, C; Abdelaziz, H; El Edrisi, M; Izham, M; Steinhoff, M; Jochebeth, A; Kuttikrishnan, S; Khan, SU; Young, M; et al.
Abstract : Background and importance: Evidence for a pharmacist role in the screening of MetS has been shown to be effective in at risk populations. 1 Despite migrants being an at risk group for the development of MetS, no literature has described screening of migrants by pharmacists. Aim and objectives: To identify the impact of the pharmacist role in screening migrants on arrival in a Middle Eastern country and following 24 months of residency in the Middle East. Material and methods: This was a prospective longitudinal observational study. Migrants aged 18–65 years were informed about the research and consented to participate by pharmacists. Baseline screening for MetS risk factors was conducted. Parameters included glycated haemoglobin (HbA1c), triglycerides (TG), high density lipoprotein cholesterol (HDL-C), blood pressure (BP) and waist circumference (WC). All migrants with identified metabolic abnormalities at this screening stage were referred to physicians by the pharmacist for further management. Migrants with normal metabolic parameters at baseline were invited to be re-screened by pharmacists. This will allow identification of an increase if any incidence of MetS and will allow for earlier intervention and management. Results: Of the 1379 identified migrants, 460 consented to participate; 70% were men and 82.2% (378) were Asians. Pharmacist led screening revealed 13.9% (64) with abnormal BP, 6.7% (31) with pre-diabetes, 21.4% (91) with elevated TG, 25% (115) with low HDL–C, 47% (219) with high WC and 16% (75) were found to have MetS and referred to the physician for follow-up. These participants were consequently identified as at risk for development of MetS at a much earlier stage. A total of 199 migrants with normal metabolic parameters will be followed-up following 24 months of residency in the Middle East. Throughout the study, migrants with metabolic abnormalities were referred by pharmacists to physicians for further management. Conclusion and relevance: The study indicates that pharmacist screening is effective for early identification and potential early management of MetS in this migrant population. References and/or acknowledgements: 1. AlAdawi RM, Tonna AP, Stewert D, et al. The impact of pharmacists' input on the screening, management and prevention of metabolic syndrome. 2018; Available at: http://www.crd.york.ac.uk/PROSPERO/display_record.php?ID=CRD42018089862. Accessed Aug 2018, 2018. No conflict of interest.